The development of identity fusion - Reese, E; Whitehouse, H (SAGE Publications, 2021)
The fusion of personal and group identities can lead to self-sacrificial pro-group behavior. Two pathways to identity fusion – via shared biology and shared experiences – have been proposed. This article elucidates a new developmental account of the origins and mechanisms of these two pathways to identity fusion from childhood to adulthood. Whereas fusion based on shared biology occurs from early childhood cued by phenotypic similarity, fusion based on episodic memories of shared experiences is not possible until mid-adolescence, and relies on suitable bonding experiences (e.g. painful initiation rituals, emotionally intense team sports, etc.). The critical development that enables fusion based on shared experiences is autobiographical reasoning, which entails connecting one’s past experiences to the present self. Autobiographical reasoning begins in adolescence, which may explain the flourishing of fusion in late adolescence and young adulthood relative to other life periods. Fusion via either pathway is linked to strong pro-group behavior, both positive and negative. We outline a program of empirical research on the development of identity fusion, while addressing relevant methodological challenges. A developmental framework may help foster efforts to harness identity fusion for peaceful rather than violent forms of self-sacrifice for the group.